Effect of body composition on physiological responses to cold-water immersion and the recovery of exercise performance - Stephens, J. M.; Halson, S. L.; Miller, J.; Slater, G. J.; Chapman, D. W.; Askew, C. D. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To explore the influence of body composition on thermal responses to cold-water immersion (CWI) and the recovery of exercise performance. Methods: Male subjects were stratified into 2 groups: low fat (LF; n=10) or high fat (HF; n=10). Subjects completed a high-intensity interval test (HIIT) on a cycle ergometer followed by a 15-min recovery intervention (control [CON] or CWI). Core temperature (Tc), skin temperature, and heart rate were recorded continuously. Performance was assessed at baseline, immediately post-HIIT, and 40 min postrecovery using a 4-min cycling time trial (TT), countermovement jump (CMJ), and isometric midthigh pull (IMTP). Perceptual measures (thermal sensation [TS], total quality of recovery [TQR], soreness, and fatigue) were also assessed. Results: Tc and TS were significantly lower in LF than in HF from 10 min (Tc, LF 36.5°C±0.5°C, HF 37.2°C±0.6°C; TS, LF 2.3±?0.5 arbitrary units [a.u.], HF 3.0±0.7 a.u.) to 40 min (Tc, LF 36.1°C±0.6°C, HF 36.8°C±0.7°C; TS, LF 2.3±0.6 a.u., HF 3.2±0.7 a.u.) after CWI (P<.05). Recovery of TT performance was significantly enhanced after CWI in HF (10.3±6.1%) compared with LF (3.1±5.6%, P=.01); however, no differences were observed between HF (6.9%±5.7%) and LF (5.4%±5.2%) with CON. No significant differences were observed between groups for CMJ, IMTP, TQR, soreness, or fatigue in either condition. Conclusion: Body composition influences the magnitude of Tc change during and after CWI. In addition, CWI enhanced performance recovery in the HF group only. Therefore, body composition should be considered when planning CWI protocols to avoid overcooling and maximize performance recovery.